A phenomenological approach to study the magnetoelectric (ME) response of lead free magnetostrictive NiFe2O4–Piezoelectric BaZr0.2Ti0.8O3 particulate composites. (October 2021) - Chavan, Pradeep
Highlights: Particulate ME composites have been synthesized by solid state reaction method. Conversion of electric into magnetic energy is responsible for potential application. NiFe2 O4 ferrite phase is a highly magnetostrictive and resistive. ME composites possess good electrical, magnetic and ME properties. Abstract: Lead-free magnetoelectric (ME) composites comprises NiFe2 O4 (NFO) and BaZr0.2 Ti0.8 O3 (BZT) were synthesized by using conventional double sintering solid-state reaction technique and it's structural, electric, dielectric, magnetic and ME properties were studied. The spectra of X-ray diffraction displayed the formation of parent phase and presence of two phases within the composites (ferrite-ferroelectric). DC resistivity as a function of temperature has been studied, it indicates the semiconducting behavior. Frequency dependent dielectric spectra of the composites indicates small polaron hopping model of conduction mechanism. Magnetic measurements at room temperature shows the composites are soft magnetic and such materials reveals M-H hysteresis type behavior. The composite with x = 0.3 showed the highest value of ME voltage coefficient ~3.82 mV/cmOe. Such ME composite materials furnish fabulous chances as prospective lead-free systems for multifunctional device applications.